The Effect of Opinion Shopping, Company Size, and Financial Performance on Going Concern Audit Opinion in Banking Companies Listed on the Indonesia Stock Exchange (Empirical Study on Banking Companies Listed on the IDX Period 2021-2023) - Siska Siska; Retno Kurnianingsih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research investigates the impact of opinion shopping, firm size, and financial performance on the issuance of going concern audit opinions. A quantitative method is employed, utilizing secondary data derived from annual financial reports published on the official website of the Indonesia Stock Exchange. The study population comprises all banking institutions listed on the Indonesia Stock Exchange between 2021 and 2023, totaling 45 companies. The sample was selected using a purposive sampling technique, resulting in 99 company observations included in the analysis. The data were analyzed using logistic regression, with statistical processing conducted through SPSS (Statistical Product and Service Solutions) version 22. The findings indicate that opinion shopping, firm size, and financial performance have a negative effect on the likelihood of receiving a going concern audit opinion.